Are peatlands cool humid islands in a landscape?. Issue 25 (12th October 2020) - Worrall, Fred; Boothroyd, Ian M.; Howden, Nicholas J. K.; Burt, Tim P.; Kohler, Tim; Gregg, Ruth
Abstract: This study proposed that due to their high standing water tables that peatlands would be cold humid islands within their landscape, and especially so relative to farmland on mineral soils. To test this hypothesis, we measured air temperature and humidity at 17 locations along a 7.8 km transect across the UK's largest lowland raised bog from February 2018 to January 2019. Air temperature and humidity were measured hourly for 1 year and supported with spot albedo measurements. The study represented a factorial experiment with respect to sites of measurement, the type of land use (peat vs. arable land) and time of sampling over both the seasonal and diurnal cycles. We show that: (a) That although mean annual temperature was not significantly different between arable and peatlands, the arable land showed a decreased amplitude to its seasonal cycle – this is the reverse of the expected pattern. (b) The albedo of the peatland was significantly lower than that of arable land showing that vegetated peatland still absorbed more solar radiation. (c) The specific humidity was lower on the peatland than on the surrounding arable land. The study showed that while shrubby vegetation exists over a peatland then energy budgets are more likely to be dominated by the lower aerodynamic resistance and lower albedo of the vegetated peatland relative to arable land. Thus, shrub‐dominated peatlands will not be a cold humid island in their landscape. Abstract :